The gospel contra Nietzsche: a South African literary critique of Wille zur Macht - F. Hale (Acta Theologica)
A century of scholarship has shed countless photons of light on the reception of Friedrich Nietzsche’s ideas in numerous countries. Still largely unilluminated, however, are South African reactions to his scepticism and moral pessimism. The present article explores how Joseph Doke, a scholarly, transplanted Englishman who served as a Baptist pastor in Johannesburg and elsewhere and wrote the first biography of Gandhi, used fiction to criticise Nietzsche early in the twentieth century. His novel The queen of the secret city (1916) embodies an explicit rejection of this German philosopher’s pivotal notion of Wille zur Macht (will to power). It is further suggested that Doke was probably indebted to G.K. Chesterton’s confrontation with that idea in Orthodoxy (1908). In Doke’s critique of Nietzsche, he also described ethnic and religious clashes and implicitly argued for the moral superiority of Christianity and the ethical need for missionary endeavours.